2019
DOI: 10.20517/2574-1225.2018.73
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic vs. open distal gastrectomy for advanced gastric cancer in elderly patients: a retrospective study

Abstract: Aim: It is unclear whether elderly patients with advanced gastric cancer can benefit from laparoscopic gastrectomy. This study aimed to compare the surgical and early postoperative outcomes of laparoscopic distal gastrectomy with those of open distal gastrectomy for advanced gastric cancer in elderly patients aged 75 years or older. Methods: We retrospectively examined all elderly patients who underwent laparoscopic distal gastrectomy or open distal gastrectomy from October 2010 to October 2017 using prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Based on the examination of titles and abstracts, 183 studies not meeting the inclusion criteria were excluded, resulting in 139 articles. After carefully reading the full texts, 20 articles that met the inclusion criteria were finally selected 12–31 . Table 1 shows the basic characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the examination of titles and abstracts, 183 studies not meeting the inclusion criteria were excluded, resulting in 139 articles. After carefully reading the full texts, 20 articles that met the inclusion criteria were finally selected 12–31 . Table 1 shows the basic characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…After carefully reading the full texts, 20 articles that met the inclusion criteria were finally selected. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]…”
Section: Study Selection and Quality Assessmentmentioning
confidence: 99%
“…Few studies about older gastric cancer patients are reported and even fewer on older patients with AGC. Yuu et al [6] reported their study to show elderly patients with AGC may benefit from laparoscopic distal gastrectomy (LDG).…”
mentioning
confidence: 99%